2021
DOI: 10.1038/s41526-021-00139-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spaceflight aboard the International Space Station on mouse estrous cycle and ovarian gene expression

Abstract: Ovarian steroids dramatically impact normal homeostatic and metabolic processes of most tissues within the body, including muscle, bone, neural, immune, cardiovascular, and reproductive systems. Determining the effects of spaceflight on the ovary and estrous cycle is, therefore, critical to our understanding of all spaceflight experiments using female mice. Adult female mice (n = 10) were exposed to and sacrificed on-orbit after 37 days of spaceflight in microgravity. Contemporary control (preflight baseline, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…A few published studies show insulin resistance parameters may change during space ight but data is con icting, suggesting either decreased insulin or no change 19 , 20 . Similarly, data on estrogen signaling are con icting with one study revealing downregulation of ESR1 and ESR2 in the uterus 21 whereas a recent study found no alterations in estrogen receptor expression in rodent ovaries 22 . To address these gaps in our knowledge of insulin and estrogen signaling in response to space ight we examined these signaling pathways across multiple tissues in rodents from the same mission as well as in a group of astronauts and a set of commercial space ight participants/astronauts.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…A few published studies show insulin resistance parameters may change during space ight but data is con icting, suggesting either decreased insulin or no change 19 , 20 . Similarly, data on estrogen signaling are con icting with one study revealing downregulation of ESR1 and ESR2 in the uterus 21 whereas a recent study found no alterations in estrogen receptor expression in rodent ovaries 22 . To address these gaps in our knowledge of insulin and estrogen signaling in response to space ight we examined these signaling pathways across multiple tissues in rodents from the same mission as well as in a group of astronauts and a set of commercial space ight participants/astronauts.…”
Section: Introductionmentioning
confidence: 93%
“…Samples were collected and processed as previously described 22 , 54 . Mouse carcasses were removed from − 80°C storage and thawed at room temperature for 15-20 minutes.…”
Section: Animal and Sample Collectionmentioning
confidence: 99%
“…Studies of female mice that were maintained on the International Space Station (ISS) for 37 days prior to euthanasia in space (eliminating re-entry stressors) revealed evidence that these female mice could be detected at different stages of the estrous cycle post-mortem, suggesting that some females were likely exhibiting estrous cyclicity [37]. Mouse embryos flown on China's SJ-10 biosatellite completed a series of cell divisions leading to blastocoel morphology during spaceflight, but both the rate of blastocyst formation and blastocyst quality were impaired [38].…”
Section: Microgravitymentioning
confidence: 99%
“…Studies have begun to assess alterations to oestrous cyclicity in association with muscle disuse and atrophy. A recent study in spaceflown mice in low earth orbit concluded that spaceflight itself does not appear to affect oestrous cyclicity (Hong et al, 2021); however, this conclusion was based on a single measurement of vaginal wall staining, which does not describe alterations to the oestrous cycle itself.…”
Section: Introductionmentioning
confidence: 98%